2022
DOI: 10.1021/acs.langmuir.2c00296
|View full text |Cite
|
Sign up to set email alerts
|

Soft Contact Mechanics with Gradient-Stiffness Surfaces

Abstract: The stiffness in the top surface of many biological entities like cornea or articular cartilage, as well as chemically cross-linked synthetic hydrogels, can be significantly lower or more compliant than the bulk. When such a heterogeneous surface comes into contact, the contacting load is distributed differently from typical contact models. The mechanical response under indentation loading of a surface with a gradient of stiffness is a complex, integrated response that necessarily includes the heterogeneity. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Recently, smart hydrogels with stimulus-responsive functions have attracted considerable attention. Briefly, stimulus-responsive hydrogels can respond to internal physiological signals (i.e., temperature [ 28 , 29 ], pH [ 30 , 31 ], redox [ 32 , 33 ], glucose [ 34 , 35 ], or enzymes [ 36 , 37 ]), external stimuli (i.e., temperature [ 38 , 39 ], magnetic field [ 40 , 41 ], pressure [ 42 , 43 ], reactive oxygen species (ROS) [ 44 , 45 ], light [ 46 , 47 ] and electric field [ 48 , 49 ]) or a combination of the above, which can reversibly or irreversibly change the physical properties or chemical structure ( Fig. 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, smart hydrogels with stimulus-responsive functions have attracted considerable attention. Briefly, stimulus-responsive hydrogels can respond to internal physiological signals (i.e., temperature [ 28 , 29 ], pH [ 30 , 31 ], redox [ 32 , 33 ], glucose [ 34 , 35 ], or enzymes [ 36 , 37 ]), external stimuli (i.e., temperature [ 38 , 39 ], magnetic field [ 40 , 41 ], pressure [ 42 , 43 ], reactive oxygen species (ROS) [ 44 , 45 ], light [ 46 , 47 ] and electric field [ 48 , 49 ]) or a combination of the above, which can reversibly or irreversibly change the physical properties or chemical structure ( Fig. 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the curves did not adhere to Hertzian contact theory at forces approximately lower than 0.5 nN. The accurate determination of surface contact for soft materials poses a significant challenge, requiring the mathematical delineation of the indentation range that accurately fits the Hertz model (Figure c). , …”
Section: Resultsmentioning
confidence: 98%
“…Indentation force measurements were performed in a 16 × 16 grid (256 total) over a 50 × 50 μm area, and two force maps were each performed on two SPMK- g -PEEK samples. Each force–displacement curve was performed with a ramp size of 5.0 μm at a 2 μms –1 indentation velocity, as used in similar soft contact research. , Data was analyzed using a custom Python script to identify the contact displacement at which the probe engaged with the surface indicated by a reduction in noise and subsequently identify the data region that complies with Hertzian contact theory to calculate elastic modulus. , The elastic modulus was calculated for only the first 1 μm of indentation to isolate substrate effects.…”
Section: Methodsmentioning
confidence: 99%
“…This shape was also confirmed by AFM observations (Figure b). With the application of AFM technologies, the surface stiffness on the hydrated polymer layer can be evaluated as shown in Figure c. , The elastic modulus of the surface of this contact lens was ∼350 kPa for the untreated silicone hydrogel contact lens and reduced to ∼30 kPa by the surface treatment. , It was found that this is equivalent to the elastic modulus of human and rabbit corneas. In addition, it was confirmed that there was no change in the elastic modulus of the surface of the contact lens after wearing it for 30 days.…”
Section: Biomimetic Design Of Silicone Hydrogel Contact Lensesmentioning
confidence: 99%